Anterior Cruciate Ligament Reconstruction with Quadrupled Semitendinosus Graft or Synthetic Ligament: Knee Stability and Clinical Outcomes at Three Years Follow-Up - Lorenzo Moretti; Giuseppe D. Cassano; Alessandro Caricato; Elio Caiaffa; Matteo D’Aprile; Francesco Angiulli; Antonio Spinarelli; Biagio Moretti; Giuseppe Solarino (Advances in Orthopedics)
The incidence of anterior cruciate ligament reconstruction (ACLR) surgeries is increasing and graft choice is important for a rapid return to activity, especially in patients older than 30 years. The aim of this study is to compare in term of quality of life and knee stability of patients who undergone ACLR using quadrupled semitendinosus (ST4) graft against patients who undergone ACLR with synthetic ligaments. Thirty-nine patients undergoing ACLR were enrolled in the study and were divided into two groups: ACLR with synthetic ligaments-LARS (group A) and ACLR with quadrupled semitendinosus graft ST4 (group B). They underwent surgery at Policlinico di Bari Orthopedic Unit between January 2017 and January 2020. Group A was composed by nineteen patients (36.16 ± 4.41 mean age-years, 22.47 ± 2.63 mean BMI-kg/m2, 39.37 ± 10.05 mean time evaluation after surgery-months) and group B was composed by twenty patients (34.95 ± 3.59 mean age-years, 21.1 ± 2.88 mean BMI-kg/m2, 36.75 ± 8.69 mean time evaluation after surgery-months). For each patient, the following data were recorded: age; side of injury, BMI, date of surgery, anterior knee laxity with the arthrometer, and Lysholm knee scoring scale. Mean value of anterior tibial translation (ATT) in group A was 3.09 mm ± 0.65 and in group B was 2.66 mm ± 1.61 (pvalue of 0.1139). Mann–-Whitney U test used to compare the Lysholm means values between groups showed a pvalue of 0.9307. LARS has comparable clinical and functional outcomes compared with hamstring autografts at short-term of 3 years follow-up. Level of Evidence: IV.